Characterization of the burden behaviour of iron ore pellets mixed with nut coke under simulated blast furnace conditions. (7th February 2020) - Gavel, Dharm Jeet; Song, Qingshi; Adema, Allert; van der Stel, Jan; Sietsma, Jilt; Boom, Rob; Yang, Yongxiang
ABSTRACT: In the blast furnace, nut coke is utilized in a mixture with the ferrous burden to improve the gas permeability. Although applied in a broad range (10–40 mm, 2–23 wt-%), limited information is available on changed burden behaviour in its presence. In the present study, the detailed characterization was performed on the iron ore pellets quenched during sintering, softening and before complete melting. The quantified information of the phase distribution across the pellets is compared for the samples mixed with and without nut coke. The principal role played by the nut coke is on bringing higher reduction and lower sintering among the pellets. For the pellet mixed with nut coke, at the core, ∼25 vol.-% of the material is observed in a network arrangement. The core structure consists of a wüstite matrix (10–20 vol.-%) reinforced with the iron nuclei (5–15 vol.-%). On the contrary, in the absence of nut coke, the pellet core is observed being hollow.